2019
DOI: 10.3390/ijms20194818
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New DR5 Agonistic Nanobodies and Generation of Multivalent Nanobody Constructs for Cancer Treatment

Abstract: Current cancer therapeutics suffer from a lack of specificity in targeting tumor cells and cause severe side effects. Therefore, the design of highly specialized drugs comprising antibody derivatives inducing apoptosis in targeted cancer cells is considered to be a promising strategy. Drugs acting on death receptor 5 (DR5) such as DR5 agonist antibodies replacing “TNF-related apoptosis-inducing ligand” (TRAIL) offer feasible opportunities in this direction. Although such agonists provided good antitumor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The choice of an appropriate linker between sdAbs is an important consideration in rational sdAb drug design and has been shown to be a decisive factor influencing the biological activity and expression. [33][34][35][36] We showed that bivalent constructs generated using a 30 GS linker or disulfide bond, as opposed to a 12 GS linker, were 35-and 169-fold less potent in enhancing TCR signaling. This could in part be explained by the lower expression levels of 2K2-30GS and highlights that potency screening of sdAb formats with different linkers when pursuing a genetic approach should take into consideration factors such as transcription, translation, post-translational modification, and secretion of the encoded sdAb.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The choice of an appropriate linker between sdAbs is an important consideration in rational sdAb drug design and has been shown to be a decisive factor influencing the biological activity and expression. [33][34][35][36] We showed that bivalent constructs generated using a 30 GS linker or disulfide bond, as opposed to a 12 GS linker, were 35-and 169-fold less potent in enhancing TCR signaling. This could in part be explained by the lower expression levels of 2K2-30GS and highlights that potency screening of sdAb formats with different linkers when pursuing a genetic approach should take into consideration factors such as transcription, translation, post-translational modification, and secretion of the encoded sdAb.…”
Section: Discussionmentioning
confidence: 95%
“…First, we increased the valency, as this strategy has been previously used to enhance the efficacy of sdAbs in cancer therapy. 33 We evaluated 3K2, a trivalent, and 2K2, a bivalent format of K2 and observed that the number of LVs encoding 2K2 that was needed to restore TCR signaling in PD-1 POS 2D3 cells upon interaction with PD-L1 POS 624-MEL cells was about 2-and 313-fold less than the number of LVs encoding 3K2 and K2, respectively. Contrary to our observations in this functional assay, 3K2 shows superior blocking abilities compared to 2K2 when delivered as protein.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the therapeutic Nb might be fused with a second Nb binding to serum albumin. Such bispecific constructs will exhibit an enhanced blood circulation time [85][86][87]. Since each Nb behaves independently, also larger multivalent constructs have been assembled, like trimeric or tetrameric Nb constructs [87].…”
Section: Genetic Fusion With Nbsmentioning
confidence: 99%
“…Notably, Rossotti et al ( 57 ) reported DNA immunization-raised EGFR nanobodies with improved functionality compared to protein immunization-raised nanobodies. Nanobodies targeting EGF ( 58 ), HER2 ( 59 , 60 ), CAIX ( 61 ), death receptor 5 (DR5) ( 62 , 63 ), c-Met ( 64 , 65 ), HGF ( 66 ), AgSK1 ( 67 ), mesothelin ( 68 ), proteasome activator complex PA28 ( 69 ), ephrin receptor A4 (EphA4) ( 70 ), CEA-cell adhesion molecule-6 (CEACAM6) ( 71 ), mitochondrial translation elongation factor (TUFM) ( 72 ), protein C receptor ( 73 ), Wnt receptors (LRP5/6) ( 74 ), and CD33 ( 75 ) have also demonstrated delayed tumor growth.…”
Section: Nanobodies As a Cancer Therapeuticsmentioning
confidence: 99%